Cross-cultural differences on Gunas and other well-being dimensions - Singh, Kamlesh; Jain, Anjali; Kaur, Jasleen; Junnarkar, Mohita; Slezackova, Alena (Asian journal of psychiatry, 2016)
Indian perspective of human nature and personality are often viewed through a trigunas perspective-Sattva, Rajas and Tamas. The current study investigated the triadic gunas and well-being dimensions across 3 nations India (n=493; 194 males and 299 females; mean age=21.73 years, SD=3.23), USA (n=302; 80 males and 222 females; mean age=22.90years, SD=2.78) and Czech Republic (n=353; 67 males and 286 females; mean age=22.29years, SD=2.29) with a total of 1148 participants. Triguna Personality (Vedic Personality inventory) and well- being dimensions measured by Mental Health Continuum- Short Form, Flourishing scale and the Scale of Positive and Negative Experiences (MHC-SF, FS and SPANE) differed across countries. Triguna were correlated with MHC-SF and its clusters, FS and SPANE. Regression analysis revealed that Trigunas accounted significantly for well-being dimensions, for instance, Sattva accounted for 48% variance in Czechs, 56% in Indians and 55% in Americans, Rajas accounted for 21% variance in Czechs, 08% in Indians and 54% in Americans and Tamas accounted for 50% variance in Czechs, 20% in Indians and 64% in Americans. The results reinforce that trigunas personality significantly predict well-being dimensions.
Keywords: Young Adult; Sattva; Cross-Cultural Comparison; Male; Tamas; mladý dospělý; Česká republika; Indie; Rajas; Adult; dospělí; mužské pohlaví; India; Czech Republic; Personality; lidé; United States; osobní uspokojení; ženské pohlaví; osobnost; Humans; Mental health; Cross-cultural; Spojené státy americké; Female; srovnání kultur; Personal Satisfaction